Os modified CoNiMoWOx / NF electro-catalytic material and preparation method thereof

Through the composite regulation of Os and oxygen-containing polymetallic surfaces, Os-CoNiMoWOx/NF electrocatalyst was prepared, which solved the problem of high energy consumption of non-Pt-based catalysts, achieved low overvoltage and high current density of electrolytic hydrogen analysis performance, and promoted electrolysis The commercial development of water hydrogen production technology.

CN119162599APending Publication Date: 2024-12-20UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466104.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing non-Pt-based electrolytic hydrogen evolution reaction catalysts have a high energy consumption under industrial-grade current density, which limits the commercial development of electrolytic hydrogen production technology.

Method used

Os and oxygen-containing polymetal surfaces are combined for design and preparation of Os-CoNiMoWOx/NF electrocatalysts. The electron conduction between polymetal oxygen-containing compounds and Os is constructed through two-step electrochemical deposition method, reducing overpotential and improving current density .

Benefits of technology

The required overpotential drops to 84mV at a current density of 1.0A/cm2. The catalyst has stable performance in 500 hours of testing, simple process and low cost, far exceeding commercial Pt/C catalysts, and has promoted the alkaline system electrolysis hydrogen production technology Commercial development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005093371200000011
    Figure HDA0005093371200000011
  • Figure HDA0005093371200000021
    Figure HDA0005093371200000021
  • Figure HDA0005093371200000022
    Figure HDA0005093371200000022
Patent Text Reader

Abstract

The invention discloses an Os modified CoNiMoWOx / NF electro-catalytic material and a preparation method thereof, and the preparation method comprises the following steps: carrying out ultrasonic treatment on foamed nickel, and then carrying out drying treatment; preparing a first electro-deposition solution; dissolving cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride in deionized water to obtain a first electro-deposition solution; the dried foamed nickel serves as a negative electrode, a graphite rod serves as a positive electrode, the dried foamed nickel and the graphite rod are placed in a first electro-deposition solution, a two-electrode system is adopted, an electrochemical potentiostatic method is used for deposition operation, a first electrode material is obtained, and the first electrode material is the foamed nickel with CoNiMoWOx / NF deposited on the surface; preparing a second electro-deposition solution; dissolving potassium hexachloroosmate into an alkaline solution to obtain a second electro-deposition solution; and the first electrode material serving as a negative electrode and a graphite rod serving as a positive electrode are placed in a second electro-deposition solution, deposition operation is carried out by adopting a two-electrode system through an electrochemical potentiostatic method, a second electrode material is obtained, and the second electrode material is foamed nickel with Os-CoNiMoWOx / NF deposited on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical catalytic energy materials, and in particular to an Os-modified CoNiMoWO x / NF electrocatalytic material and preparation method thereof. Background Art

[0002] With the rapid development of social industrialization, human demand for fossil energy has increased year by year. However, the storage of fossil energy in the earth's crust is limited, so the development of alternative energy is urgent. In recent years, hydrogen energy has received widespread attention due to its high calorific value and clean advantages, and is regarded as an important part of future energy deployment. The preparation of hydrogen energy mainly includes hydrogen production from fossil raw materials and hydrogen production from renewable energy. The former does not reduce the use of fossil energy, while the latter uses light energy, wind energy and water electrolysis to achieve hydrogen production. Light energy and wind energy cannot achieve a sustainable development strategy for hydrogen production due to the influence of regional climate, while water electrolysis hydrogen production technology is simple and not affected by factors such as climate, so it is an effective technology for sustainable hydrogen production.

[0003] The hydrogen evolution reaction is an important half-reaction of water electrolysis to produce hydrogen. In order to reduce the polarization potential during the reaction, a catalyst is usually required. Pt (platinum) is an ideal catalyst for the hydrogen evolution reaction, but its high price restricts its large-scale commercial use. The preparation of efficient and low-cost non-Pt-based catalysts is crucial to the development of commercial water electrolysis. However, the current study reports that the catalysts for the hydrogen evolution reaction are only 1.0 A / cm 2 The energy consumption required at industrial-grade current density (greater than 200mV) is still high. Summary of the invention

[0004] In view of the important scientific problem faced by the catalyst for the hydrogen evolution reaction of water electrolysis, namely, the high energy consumption of industrial-grade current density of non-Pt-based catalysts, the present invention proposes for the first time a composite regulation strategy of Os (osmium) and oxygen-containing multi-metal surfaces, and designs and prepares Os-CoNiMoWO by using Os with the same period and similar outer d orbital electronic structure as Pt. x / NF (Os represents osmium, Co represents cobalt, Ni represents nickel, Mo represents molybdenum, W represents tungsten, O represents oxygen, and NF represents nickel foam) electrocatalyst, constructs the electron conduction between the multi-metallic oxygen-containing compound and Os, so that the catalyst has a current density of 1.0A / cm in 1.0M KOH (i.e., potassium hydroxide with a concentration of 1 mol per liter) electrolyte. 2 The required overpotential is only 84mV. At the same time, after 500 hours of long-term stability testing, the catalyst still has stable performance.

[0005] To achieve the above objectives, the present invention provides an Os-modified CoNiMoWO xPreparation method of / NF electrocatalytic material, Os modified CoNiMoWO x The preparation method of the / NF electrocatalytic material comprises the following steps:

[0006] Step S10: ultrasonically treating the nickel foam, and then drying it;

[0007] Step S20: preparing a first electrodeposition solution; dissolving cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride in deionized water to obtain the first electrodeposition solution;

[0008] Step S30: The dried nickel foam is used as the negative electrode and the graphite rod is used as the positive electrode in the first electrodeposition solution, and a two-electrode system is used to perform deposition using an electrochemical constant potential method to obtain a first electrode material. The first electrode material is a material having CoNiMoWO deposited on the surface. x / NF nickel foam;

[0009] Step S40: preparing a second electrodeposition solution; dissolving potassium hexachloroosmate in an alkaline solution to obtain the second electrodeposition solution;

[0010] Step S50: The first electrode material is used as the negative electrode, and the graphite rod is used as the positive electrode, and is placed in the second electrodeposition solution, and a two-electrode system is used to perform a deposition operation using an electrochemical constant potential method to obtain a second electrode material, wherein the second electrode material has Os-CoNiMoWO deposited on the surface. x / NF nickel foam.

[0011] As a preferred embodiment, in step S10, the step of ultrasonically treating the nickel foam includes: immersing the nickel foam in a dilute hydrochloric acid solution for ultrasonic treatment for 10 minutes, washing with deionized water and then transferring to an anhydrous ethanol solution for ultrasonic treatment for 10 minutes; the step of drying includes: placing the ultrasonically treated nickel foam in a vacuum drying oven for drying, and the temperature in the vacuum drying oven is 60°C.

[0012] As a preferred implementation, in step S20, the molar ratio of cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride is 24:24:12:1:24.

[0013] As a preferred implementation, in step S20, the concentration of cobalt nitrate in the first electrodeposition solution is 0.03 mol / L.

[0014] As a preferred implementation, in step S30, the voltage of the electrochemical constant potential method is 5V, and the duration of the deposition operation is 20 minutes.

[0015] As a preferred embodiment, in step S30, after the deposition operation is completed, the nickel foam is cleaned with deionized water and transferred to a vacuum drying oven at 60° C. for drying to obtain the first electrode material.

[0016] As a preferred implementation, in step S40, the concentration of potassium hexachloroosmate in the second electrodeposition solution is 0.5 g / L to 1 g / L.

[0017] As a preferred embodiment, in step S50, the voltage of the electrochemical constant potential method is 4V, and the deposition operation time is 20 minutes; after the deposition operation is completed, the nickel foam is washed with deionized water and transferred to a vacuum drying oven at 60°C for drying to obtain the second electrode material.

[0018] As a preferred embodiment, in step S10, the area of ​​the nickel foam is 2×3 cm 2 In step S20, the volume of the deionized water is 50 ml; in step S40, the volume of the alkaline solution is 50 ml; in steps S30 and S50, the area of ​​the negative electrode immersed in the solution is 2×2 cm 2 .

[0019] The present application embodiment provides an Os-modified CoNiMoWO x / NF electrocatalytic material, the Os-modified CoNiMoWO x The / NF electrocatalytic material is prepared by the preparation method described in any of the above embodiments.

[0020] Beneficial effects:

[0021] The Os-modified CoNiMoWO provided in this embodiment x / NF electrocatalytic material preparation method, through a simple and convenient two-step electrochemical deposition method to finally obtain Os-modified CoNiMoWO x / NF electrocatalytic material, which has a low overvoltage of 86mV and can reach an industrial-grade current density, which is much better than commercial Pt / C (platinum carbon catalyst) and other comparative materials. 2 The high current density can be maintained for 500 hours, which is a promising alkaline hydrogen reduction electrocatalyst. The preparation method is simple, low-cost, and can be prepared on a large scale. It overcomes the cumbersome disadvantages of the electrode preparation process in the same field and is expected to promote the commercial development of hydrogen production technology by electrolysis of water in alkaline systems.

[0022] With reference to the following description and the accompanying drawings, the specific embodiments of the present invention are disclosed in detail, indicating the manner in which the principles of the present invention can be adopted. It should be understood that the embodiments of the present invention are not limited in scope thereby.

[0023] Features described and / or illustrated with respect to one embodiment may be used in the same or similar manner in one or more other embodiments, combined with features in other embodiments, or substituted for features in other embodiments.

[0024] It should be emphasized that the term “include / comprises” when used herein refers to the presence of features, integers, steps or components, but does not exclude the presence or addition of one or more other features, integers, steps or components. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 is an Os-modified CoNiMoWO provided in this embodiment. x / Flow chart of the steps of the preparation method of NF electrocatalytic material;

[0027] Figure 2 for Figure 1 A SEM (scanning electron microscope) image of the first electrode material obtained in step S30;

[0028] Figure 3 for Figure 1 SEM image of the second electrode material obtained in step S50;

[0029] Figure 4 for Figure 1 XRD (X-ray diffraction) spectra of the first electrode material obtained in step S30 and the second electrode material obtained in step S50;

[0030] Figure 5 NF, CoNiMoWO x / NF、Pt / C、Os-CoNiMoO x / NF、Os-CoNiMoWO x / NF、Os-CoNiWO x LSV (Linear Sweep Voltammetry) polarization curve of / NF;

[0031] Figure 6 CoNiMoWO x / NF、Pt / C、Os-CoNiMoO x / NF、Os-CoNiMoWO x / NF、Os-CoNiWO x / NF at different current densities (0.5A / cm 2 and 1.0A / cm 2 ) overpotential comparison diagram;

[0032] Figure 7 CoNiMoWO x / NF、Pt / C、Os-CoNiMoO x / NF、Os-CoNiMoWO x / NF、Os-CoNiWO x Electrochemical impedance spectroscopy of / NF;

[0033] Figure 8 The second electrode material (Os-CoNiMoWO x / NF) performance stability diagram. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0035] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be another element centered thereon. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be another element centered thereon at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0037] See also Figure 1 The present application provides an Os-modified CoNiMoWO xThe preparation method of the / NF electrocatalytic material comprises the following steps:

[0038] Step S10: After ultrasonic treatment, the nickel foam is dried.

[0039] Specifically, the nickel foam can be commercial nickel foam. The step of ultrasonically treating the nickel foam includes: immersing the nickel foam in a dilute hydrochloric acid solution for ultrasonic treatment for 10 minutes, washing with deionized water and then transferring to an anhydrous ethanol solution for ultrasonic treatment for 10 minutes. The step of drying includes: placing the nickel foam after ultrasonic treatment in a vacuum drying oven for drying, and the temperature in the vacuum drying oven is 60°C.

[0040] Step S20: preparing a first electrodeposition solution.

[0041] Specifically, cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride are dissolved in deionized water to obtain the first electrodeposition solution.

[0042] The molar ratio of cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride is 24:24:12:1:24, so that a first electrodeposition solution that meets the requirements can be obtained.

[0043] Preferably, the concentration of cobalt nitrate in the first electrodeposition solution is 0.01-0.05 mol / L, which can make the subsequent electrochemical deposition process smoother. More preferably, the concentration of cobalt nitrate in the first electrodeposition solution is 0.03 mol / L.

[0044] It should be noted that there is no unique restriction on the order between step S20 and step S10, and it is only necessary to ensure that step S20 and step S10 are both performed before step S30.

[0045] Step S30: The dried nickel foam is used as the negative electrode and the graphite rod is used as the positive electrode in the first electrodeposition solution, and a two-electrode system is used to perform deposition using an electrochemical constant potential method to obtain a first electrode material. The first electrode material is a material having CoNiMoWO deposited on the surface. x / NF nickel foam.

[0046] Specifically, the positive electrode of the DC power supply is connected to the graphite rod, and the negative electrode of the DC power supply is connected to the nickel foam treated in step S10. When using the electrochemical constant potential method, the selected voltage is 5V, and the duration of the deposition operation is preferably 20 minutes. After the deposition operation is completed, the nickel foam is washed with deionized water and transferred to a vacuum drying oven at 60°C for drying to obtain the first electrode material.

[0047] Step S40: preparing a second electrodeposition solution.

[0048] Specifically, potassium hexachloroosmate is dissolved in an alkaline solution to obtain the second electrodeposition solution. The concentration of potassium hexachloroosmate in the second electrodeposition solution is preferably 0.5 g / L to 1 g / L, which can ensure that the subsequent electrochemical deposition process proceeds smoothly. The alkaline solution is preferably a KOH solution or a NaOH solution.

[0049] It should be noted that there is no unique restriction on the order between step S40 and step S30 , and it is only necessary to ensure that step S40 and step S30 are both performed before step S50 .

[0050] Step S50: The first electrode material is used as the negative electrode, and the graphite rod is used as the positive electrode, and is placed in the second electrodeposition solution, and a two-electrode system is used to perform a deposition operation using an electrochemical constant potential method to obtain a second electrode material, wherein the second electrode material has Os-CoNiMoWO deposited on the surface. x / NF nickel foam.

[0051] Among them, Os-CoNiMoWO deposited on the surface of the second electrode material x / NF is the electrocatalytic material to be prepared by the preparation method of the present application.

[0052] In step S50, the positive electrode of the DC power supply is connected to the graphite rod, and the negative electrode of the DC power supply is connected to the first electrode material. The voltage of the electrochemical constant potential method is preferably 4V, and the duration of the deposition operation is preferably 20 minutes. After the deposition operation is completed, the nickel foam is washed with deionized water and transferred to a vacuum drying oven at 60°C for drying to obtain the second electrode material.

[0053] The Os-modified CoNiMoWO provided in this embodiment x / NF electrocatalytic material preparation method, through a simple and convenient two-step electrochemical deposition method to finally obtain Os-modified CoNiMoWO x / NF electrocatalytic material, which has a low overvoltage of 86mV and can reach industrial-grade current density, which is much better than commercial Pt / C (platinum carbon catalyst) and other comparative materials. 2 The high current density can be maintained for 500 hours, which is a promising alkaline hydrogen reduction electrocatalyst. The preparation method is simple, low-cost, and can be prepared on a large scale. It overcomes the cumbersome disadvantages of the electrode preparation process in the same field and is expected to promote the commercial development of hydrogen production technology by electrolysis of water in alkaline systems.

[0054] In a specific embodiment, the area of ​​the nickel foam selected in step S10 is 2×3 cm 2. In step S20, the volume of deionized water is 50 ml, and the amounts of cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride in the first electrodeposition solution are 1.5 mmol, 1.5 mmol, 0.75 mmol, 0.0625 mmol and 1.5 mmol respectively. In step S40, the volume of alkaline solution is 50 ml, and the amount of potassium hexachloroosmate in the second electrodeposition solution is 25-50 mg. In steps S30 and S50, the area of ​​the negative electrode immersed in the solution is 2×2 cm 2 .

[0055] like Figure 2 As shown, the microscopic morphology of the first electrode material presents a nanosheet array structure. Figure 3 As shown, the microscopic appearance of the second electrode material still presents a nanosheet array structure, that is, the morphology of the catalyst obtained by the preparation method of the present application is a two-dimensional nanosheet array coated and grown on the surface of the nickel foam skeleton. Figure 4 The above spectrum shows that Os has a significant effect on CoNiMoWO x No new phase was produced before and after / NF modification, and the structure was still amorphous. The two strong peaks in the spectrum belonged to the base nickel foam.

[0056] In order to illustrate the Os-modified CoNiMoWO prepared by this preparation method x The excellent performance of NF electrocatalytic material is compared with the following three materials:

[0057] 1. Pt / C (containing 20% ​​Pt) powder material.

[0058] 2. Os-CoNiMoO x / NF electrocatalytic materials;

[0059] 3. Os-CoNiWO x / NF electrocatalytic materials.

[0060] Among them, Pt / C (containing 20% ​​Pt) powder material can be purchased directly.

[0061] Os-CoNiMoO x The method for obtaining the NF electrocatalytic material is as follows:

[0062] Step S11: the same as the above step S10;

[0063] Step S21: dispersing and dissolving 1.5 mmol of cobalt nitrate, 1.5 mmol of nickel nitrate, 1.5 mmol of sodium molybdate and 1.5 mmol of ammonium fluoride in 50 ml of deionized water to obtain a third electrodeposition solution;

[0064] Step S31: Place the nickel foam obtained in step S11 as the negative electrode and the graphite rod as the positive electrode in the third electrodeposition solution, with the area of ​​the negative electrode immersed in the solution being 2×2 cm 2 The two-electrode system was used to perform the deposition operation at 5 V for 20 minutes using the electrochemical constant potential method. After the deposition, the negative electrode was cleaned with deionized water and transferred to a vacuum drying oven at 60 ° C for drying to obtain CoNiMoO x / NF electrode materials;

[0065] Step S41: the same as the above step S40;

[0066] Step S51: CoNiMoO x / NF electrode material as the negative electrode and graphite rod as the positive electrode were placed in the second electrodeposition solution, and the area of ​​the negative electrode immersed in the solution was 2×2 cm 2 The deposition operation was carried out at 4 V for 20 minutes using a two-electrode system using an electrochemical constant potential method. After the deposition, the negative electrode was washed with deionized water and transferred to a vacuum drying oven at 60 °C for drying to obtain Os-CoNiMoO x / NF electrode materials.

[0067] Os-CoNiWO x The method for obtaining the NF electrocatalytic material is as follows:

[0068] Step S12: the same as the above step S10;

[0069] Step S22: dispersing and dissolving 1.5 mmol of cobalt nitrate, 1.5 mmol of nickel nitrate, 0.125 mmol of ammonium metatungstate and 1.5 mmol of ammonium fluoride in 50 ml of deionized water to obtain a fourth electrodeposition solution;

[0070] Step S32: Place the nickel foam obtained in step S12 as the negative electrode and the graphite rod as the positive electrode in the fourth electrodeposition solution, with the area of ​​the negative electrode immersed in the solution being 2×2 cm 2 The two-electrode system was used to perform the deposition operation at 5V for 20 minutes using the electrochemical constant potential method. After the deposition, the negative electrode was cleaned with deionized water and transferred to a vacuum drying oven at 60°C for drying to obtain CoNiWO x / NF electrode materials;

[0071] Step S42: the same as the above step S40;

[0072] Step S52: CoNiWO x / NF electrode material as the negative electrode and graphite rod as the positive electrode were placed in the second electrodeposition solution, and the area of ​​the negative electrode immersed in the solution was 2×2 cm 2The deposition operation was carried out at 4 V for 20 minutes using a two-electrode system using an electrochemical constant potential method. After the deposition, the negative electrode was cleaned with deionized water and transferred to a vacuum drying oven at 60 ° C for drying to obtain Os-CoNiWO x / NF electrode materials.

[0073] like Figure 5 As shown, electrochemical LSV tests need to be performed on each material. For Pt / C, 5 mg of Pt / C powder can be weighed and evenly dispersed in a mixed solution of 600 μl of anhydrous ethanol, 300 μl of deionized water, and 100 μl of Nafion to prepare a catalyst slurry; then 100 μl of the above slurry is evenly coated on an area of ​​1x1 cm 2 The size of the nickel foam surface treated in step S10 is cut into convex-shaped electrode sheets after natural drying, with a working area of ​​0.25 cm 2 A three-electrode system was used to perform electrochemical LSV tests (-0.8 V to -3.0 V vs. Hg / HgO; scan rate was 5 mV / s) with the electrode sheet as the working electrode, a graphite rod as the counter electrode, a mercury / mercury oxide electrode as the reference electrode, and 1.0 M KOH as the electrolyte.

[0074] For the Os-modified CoNiMoWO prepared in the embodiment of the present application x / NF electrocatalytic material, and used it as the working electrode to test the performance of hydrogen evolution reaction in alkaline water electrolysis using a three-electrode system. Specifically, the second electrode material was cut into a convex shape with a test area of ​​0.25 cm 2 As the working electrode, it was placed in a single-cell electrolytic cell together with a mercury / mercury oxide electrode and a graphite rod. The HER (electrocatalyst hydrogen evolution reaction) performance was tested by linear sweep voltammetry (-0.8 V to -3.0 V vs. Hg / HgO) in a 1.0 M KOH solution. 2 Evaluate the stability of the material.

[0075] For Os-CoNiMoO x / NF electrocatalytic materials, using a three-electrode system to deposit Os-CoNiMoO x Electrochemical LSV test (-0.8 V to -3.0 V vs. Hg / HgO; scan rate of 5 mV / s) was performed using nickel foam of / NF as the working electrode, graphite rod as the counter electrode, mercury / mercury oxide electrode as the reference electrode, and 1.0 M KOH as the electrolyte.

[0076] For Os-CoNiWO x / NF electrocatalytic materials, using a three-electrode system to deposit Os-CoNiWO xElectrochemical LSV test (-0.8 V to -3.0 V vs. Hg / HgO; scan rate of 5 mV / s) was performed using nickel foam of / NF as the working electrode, graphite rod as the counter electrode, mercury / mercury oxide electrode as the reference electrode, and 1.0 M KOH as the electrolyte.

[0077] from Figure 5 It can be seen that Os-CoNiMoWO x The potential required for the alkaline hydrogen evolution performance of the Pt / NF electrode material is significantly lower than that of commercial Pt / C and other comparative electrode materials, indicating that the second electrode material obtained in the present application has great advantages in alkaline hydrogen evolution.

[0078] It can be clearly seen from FIG. 6 that the second electrode material obtained in the present application requires the lowest overpotential at the same current density, indicating that the energy consumption required to release the same amount of hydrogen is the lowest.

[0079] from Figure 7 It can be seen that the second electrode material obtained in the present application exhibits the smallest impedance, which also means that the electron transfer rate of its surface intermediate is faster.

[0080] from Figure 8 It can be seen that the second electrode material obtained in this application has an 2 It can run stably for 500 hours at industrial-grade current density.

[0081] In summary, the second electrode material obtained by the preparation method provided in the present application has industrial-grade hydrogen reduction performance and stability of up to 500 hours. At the same time, through the performance comparison between commercial materials and electrode materials, it is found that the catalyst material (second electrode material) has strong competitiveness in the actual commercial field of alkaline water electrolysis hydrogen reduction.

[0082] Based on the same concept, the present invention also provides an Os-modified CoNiMoWO x / NF electrocatalytic material, the Os-modified CoNiMoWO x / NF electrocatalytic materials are composed of any of the above Os-modified CoNiMoWO x / NF electrocatalytic material is prepared by the preparation method.

[0083] In this embodiment, the Os-modified CoNiMoWO x The implementation method of the / NF electrocatalytic material corresponds to the implementation method of the preparation method, which can solve the technical problems solved by the implementation method of the preparation method and correspondingly achieve the technical effects of the implementation method of the preparation method. The specific details of this application will not be repeated here.

[0084] It should be noted that, in the description of this specification, the terms "first", "second", etc. are only used for descriptive purposes and to distinguish similar objects. There is no order of precedence between the two, and they cannot be understood as indicating or implying relative importance. In addition, in the description of this specification, unless otherwise specified, the meaning of "plurality" is two or more.

[0085] Any numerical value cited herein includes all values ​​of lower and upper values ​​that increase by one unit from the lower limit to the upper limit, and there is at least a two-unit interval between any lower value and any higher value. For example, if the value of the quantity of a component or a process variable (such as temperature, pressure, time, etc.) is stated to be from 1 to 90, preferably from 20 to 80, and more preferably from 30 to 70, the purpose is to illustrate that values ​​such as 15 to 85, 22 to 68, 43 to 51, 30 to 32 are also explicitly listed in the specification. For values ​​less than 1, one unit is appropriately considered to be 0.0001, 0.001, 0.01, 0.1. These are merely examples that are intended to be clearly expressed, and it can be considered that all possible combinations of numerical values ​​listed between the lowest value and the highest value are clearly stated in the specification in a similar manner.

[0086] Unless otherwise indicated, all ranges include the endpoints and all numbers between the endpoints. "About" or "approximately" used with a range applies to both endpoints of the range. Thus, "about 20 to 30" is intended to cover "about 20 to about 30", including at least the specified endpoints.

[0087] All articles and references disclosed, including patent applications and publications, are incorporated herein by reference for all purposes. The term "consisting essentially of..." to describe a combination should include the identified elements, ingredients, parts or steps and other elements, ingredients, parts or steps that do not substantially affect the basic novel characteristics of the combination. The use of the terms "comprising" or "including" to describe a combination of elements, ingredients, parts or steps herein also contemplates embodiments that consist essentially of these elements, ingredients, parts or steps. By using the term "may", it is intended to indicate that any attribute described that "may" include is optional.

[0088] Multiple elements, ingredients, parts or steps can be provided by a single integrated element, ingredient, part or step. Alternatively, a single integrated element, ingredient, part or step can be divided into separate multiple elements, ingredients, parts or steps. The disclosure "one" or "an" used to describe an element, ingredient, part or step is not intended to exclude other elements, ingredients, parts or steps.

[0089] It should be understood that the above description is for illustration and not for limitation. Many embodiments and many applications beyond the examples provided will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of the present teachings should not be determined with reference to the above description, but should be determined with reference to the appended claims and the full scope of equivalents possessed by such claims. For the purpose of comprehensiveness, all articles and references, including disclosures of patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the preceding claims is not intended to be a waiver of the subject matter, nor should it be considered that the inventors did not consider the subject matter to be part of the disclosed inventive subject matter.

Claims

1. An Os-modified CoNiMoWO x / NF electrocatalytic material preparation method, It is characterized in that The following steps are involved: step S10: After ultrasonic treatment of the nickel foam, drying is performed; Step S20: preparing a first electrodeposition solution; dissolving cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride in deionized water to obtain the first electrodeposition solution; Step S30: The dried nickel foam is used as the negative electrode and the graphite rod is used as the positive electrode in the first electrodeposition solution, and a two-electrode system is used to perform deposition using an electrochemical constant potential method to obtain a first electrode material. The first electrode material is a material having CoNiMoWO deposited on the surface. x / NF nickel foam; Step S40: preparing a second electrodeposition solution; dissolving potassium hexachloroosmate in an alkaline solution to obtain the second electrodeposition solution; Step S50: The first electrode material is used as the negative electrode, and the graphite rod is used as the positive electrode, and is placed in the second electrodeposition solution, and a two-electrode system is used to perform a deposition operation using an electrochemical constant potential method to obtain a second electrode material, wherein the second electrode material has Os-CoNiMoWO deposited on the surface. x / NF nickel foam.

2. Os-modified CoNiMoWO according to claim 1 x / NF electrocatalytic material preparation method, It is characterized in that In step S10, the step of ultrasonically treating the nickel foam includes: immersing the nickel foam in a dilute hydrochloric acid solution for ultrasonic treatment for 10 minutes, washing with deionized water and then transferring to an anhydrous ethanol solution for ultrasonic treatment for 10 minutes; the step of drying includes: placing the nickel foam after ultrasonic treatment in a vacuum drying oven for drying, and the temperature in the vacuum drying oven is 60°C.

3. Os-modified CoNiMoWO according to claim 1 x / NF electrocatalytic material preparation method, It is characterized in that In step S20, the molar ratio of cobalt nitrate, nickel nitrate, sodium molybdate, ammonium metatungstate and ammonium fluoride is 24:24:12:1:

24.

4. Os-modified CoNiMoWO according to claim 3 x / NF electrocatalytic material preparation method, It is characterized in that In step S20, the concentration of cobalt nitrate in the first electrodeposition solution is 0.03 mol / L.

5. Os-modified CoNiMoWO according to claim 1 x / NF electrocatalytic material preparation method, It is characterized in that In step S30 , the voltage of the electrochemical constant potential method is 5 V, and the duration of the deposition operation is 20 minutes.

6. Os-modified CoNiMoWO according to claim 5 x / NF electrocatalytic material preparation method, It is characterized in that In step S30, after the deposition operation is completed, the foamed nickel is cleaned with deionized water and transferred to a vacuum drying oven at 60°C for drying to obtain the first electrode material.

7. The Os-modified CoNiMoWO according to claim 1 x / NF electrocatalytic material preparation method, It is characterized in that In step S40, the concentration of potassium hexachloroosmate in the second electrodeposition solution is 0.5 g / L to 1 g / L.

8. The Os-modified CoNiMoWO according to claim 1 x / NF electrocatalytic material preparation method, It is characterized in that In step S50, the voltage of the electrochemical constant potential method is 4V, and the duration of the deposition operation is 20 minutes; After the deposition operation is completed, the nickel foam is washed with deionized water and transferred to a vacuum drying oven at 60° C. for drying to obtain the second electrode material.

9. The Os-modified CoNiMoWO according to claim 1 x / NF electrocatalytic material preparation method, It is characterized in that In step S10, the area of ​​the nickel foam is 2×3 cm 2 In step S20, the volume of the deionized water is 50 ml; in step S40, the volume of the alkaline solution is 50 ml; in steps S30 and S50, the area of ​​the negative electrode immersed in the solution is 2×2 cm 2 .

10. An Os-modified CoNiMoWO x / NF electrocatalytic materials, It is characterized in that The Os-modified CoNiMoWO x The / NF electrocatalytic material is prepared by the preparation method described in any one of claims 1-9.